The All but Forgotten Mascagni–Sappey Pathway: Learning from Immediate Lymphatic Reconstruction - Johnson, Anna Rose; Bravo, Miguel G.; James, Ted A.; Suami, Hiroo; Lee, Bernard T.; Singhal, Dhruv (Journal of Reconstructive Microsurgery, 2020)
Background Upper extremity lymphedema occurs in 25 to 40% of patients after axillary lymph node dissection (ALND). Immediate lymphatic reconstruction (ILR) or the lymphatic micro- surgical preventative healing approach has demonstrated a significant decrease in postoperative rates of lymphedema (LE) from 4 to 12%. Our objective was to map the Mascagni -Sappey pathway, the lateral upper arm draining lymphatics, in patients undergoing ILR to better characterize the drainage pattern of this lymphosome to the axilla.Methods A retrospective review of our institutional lymphatic database was conducted and consecutive breast cancer patients undergoing ILR were identified from November 2017 through June 2018. Patient demographics, clinical characteristics, and intraoperative records were retrieved and analyzed.Results Twenty-nine consecutive breast cancer patients who underwent ILR after ALND were identified. Patients had a mean age of 54.6years and body mass index (BMI) of 26.6 kg/m2. Fluorescein isothiocyanate (FITC) was injected at the medial upper arm and isosulfan blue was injected at the cephalic vein, or lateral upper arm, prior to ALND. After ALND, an average 2.5 divided lymphatics were identified, and a mean 1.2 lymphatics were bypassed. In all patients, divided FITC lymphatics were identified. However, in only three patients (10%), divided blue lymphatics were identified after ALND.Conclusion In this study, variable drainage of the lateral upper arm to the axillary bed was noted. This study is the first to provide a description of intraoperative findings, demonstrating variable drainage patterns of upper extremity lymphatics to the axilla. Moreover, we noted that the lateral- and medial-upper arm lymphosomes have mutually exclusive pathways draining to the axilla. Further study of lymphatic anatomy variability may elucidate the pathophysiology of lymphedema development and influence approaches to immediate lymphatic reconstruction.
Keywords: immediate lymphatic reconstruction; anatomy; imaging; lymphatic drainage